Study on the characteristics of gas permeability of coal under loaded stress - Qu, Dengxing; Li, Xinping; Zhang, Jianhua; Li, Dengke; Wang, Gongzhong (Penerbit Universiti Kebangsaan Malaysia, 2017)
The #3 coal seam of Jinsheng Rundong Ltd. of Jin-Coal Group in Shanxi Province, China, has high gas content and pressure; however, it has a low gas permeability, which can easily cause gas enrichment and may cause accidents of coal and gas outbursts. In this work, the characteristics of gas seepage were thoroughly studied by designing and modifying the ‘complete stress-strain tri-axial servo temperature-controlled test system’. The study was conducted based on four factors: Axial pressure, confining pressure, effective stress and gas pressure. We found that the axial pressure has a weak impact on coal gas permeability, indicated by a linear relationship. The confining pressure, however, has a strong impact on gas permeability, showing an exponential relationship. The relationship between permeability and gas pressure was identified as a second-order polynomial function. The functional relationship between gas permeability and axial pressure, confining pressure, effective stress, gas pressure was analyzed. Investigation into the natural flow rate of gas, concentration of gas drainage and damping coefficient supported the conclusion from the experimental study on the characteristics of gas seepage under loaded stress.